Combining experiment and computation to elucidate the optical properties of Ce3+ in Ba5Si8O21. Issue 4 (14th January 2020) - Zhong, Jiyou; Hariyani, Shruti; Zhuo, Ya; Zhao, Weiren; Liu, Xiang; Wen, Jun; Brgoch, Jakoah
Abstract : A comprehensive study of a new and complex inorganic silicon-based luminescent material through computational and experimental methods. Abstract : Complex alkaline earth silicates have been extensively studied as rare-earth substituted phosphor hosts for use in solid-state lighting. One of the biggest challenges facing the development of new phosphors is understanding the relationship between the observed optical properties and the crystal structure. Fortunately, recent improvements in characterization techniques combined with advances in computational methodologies provide the research tools necessary to conduct a comprehensive analysis of these systems. In this work, a new Ce 3+ substituted phosphor is developed using Ba5 Si8 O21 as the host crystal structure. The compound is evaluated using a combination of experimental and computational methods and shows Ba5 Si8 O21 :Ce 3+ adopts a monoclinic crystal structure that was confirmed through Rietveld refinement of high-resolution synchrotron powder X-ray diffraction data. Photoluminescence spectroscopy reveals a broad-band blue emission centered at ∼440 nm with an absolute quantum yield of ∼45% under ultraviolet light excitation ( λ ex = 340 nm). This phosphor also shows a minimal chromaticity-drift but with moderate thermal quenching of the emission peak at elevated temperatures. The modest optical response of this phase is believed to stem from a combination of intrinsic structural complexity and the formation of defects because of the aliovalent rare-earth substitution. Finally, computational modeling provides essential insight into the site preference and energy level distribution of Ce 3+ in this compound. These results highlight the importance of using experiment and computation in tandem to interpret the relationship between observed optical properties and the crystal structures of all rare-earth substituted complex phosphors.